2004
DOI: 10.1111/j.1467-940x.2004.00082.x
|View full text |Cite
|
Sign up to set email alerts
|

Regional Convergence and the Economic Performance of Peripheral Areas in Turkey

Abstract: The objective of this paper is to examine regional convergence and core‐periphery relations in Turkey. The main question explores the degree to which there has been a transformation of interregional disparities in terms of “convergence” and performance of peripheral regions in Turkey by considering GDP per capita over the 1980‐97 period. As a result of σ and β convergence (absolute and conditional) analyses, following Barro and Sala‐i‐Martin (1995), there is no evidence for convergence across both provinces an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
91
0
13

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 146 publications
(110 citation statements)
references
References 39 publications
6
91
0
13
Order By: Relevance
“…The analysis of Gezici and Hewings (2001) revealed that the dispersion of GDP per capita across the provinces and functional regions have similar trends with little evidence of convergence. The growth rate and initial levels are essentially uncorrelated across the provinces and functional regions resulting in the rejection of β convergence for the 1980-97 period (see Barro and Sala-i-Martin, 1995 for a review of the various types of convergence).…”
Section: Motivation and Expectationsmentioning
confidence: 99%
See 3 more Smart Citations
“…The analysis of Gezici and Hewings (2001) revealed that the dispersion of GDP per capita across the provinces and functional regions have similar trends with little evidence of convergence. The growth rate and initial levels are essentially uncorrelated across the provinces and functional regions resulting in the rejection of β convergence for the 1980-97 period (see Barro and Sala-i-Martin, 1995 for a review of the various types of convergence).…”
Section: Motivation and Expectationsmentioning
confidence: 99%
“…These policy conflicts have neutralized many attempts to reduce regional disparities and have sustained core-periphery disparities. The result of the spatial correlation analysis provides evidence that the disparities between east and west regions remain (see Gezici and Hewings, 2001). In this paper, the level of the spatial analysis of regional inequalities in Turkey is developed not only at the inter-provincial level but for three different regional definitions as well.…”
Section: Motivation and Expectationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, there have been a number of studies on regional convergence regarding Turkey (see, for example, Filiztekin, 1998, Yildirim, 2005, Gezici and Hewings, 2004. Although there are several studies analysing regional convergence in Turkey, there appears limited number of studies that investigates the impact of the public capital on the private sector performance and regional convergence (see Önder et.al.…”
Section: Introductionmentioning
confidence: 99%